2009
DOI: 10.1051/0004-6361/200912091
|View full text |Cite
|
Sign up to set email alerts
|

COSMOS 5921+0638: characterization and analysis of a new strong gravitationally lensed AGN

Abstract: Context. Strong lens candidates have been newly identified within the COSMOS field. We present VLT/FORS1 spectroscopic followup observations and HST/WFPC2 imaging of the system COSMOS 5921+0638, which exhibits quadruply lensed images and a perfect Einstein ring. Aims. We investigate the nature of COSMOS 5921+0638 by studying its photometric, spectroscopic and physical properties. Methods. By analyzing our VLT/FORS1 spectroscopy and Subaru/CFHT/HST imaging of COSMOS 5921+0638, we completed both an environmental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…There are three known lenses in the HSC S16A footprint found again by Chitah: HSCJ092455+021923 (Inada et al 2012), HSCJ095921+020638 (Anguita et al 2009), and HSCJ115252+004733 (More et al 2017) 3 . We include two new lens candidates, HSCJ091148+041852 and HSCJ141136−010216, found by YattaLens but missed in Chitah's classification 4 , for X-shooter spectroscopic followup.…”
Section: Other Candidatesmentioning
confidence: 86%
“…There are three known lenses in the HSC S16A footprint found again by Chitah: HSCJ092455+021923 (Inada et al 2012), HSCJ095921+020638 (Anguita et al 2009), and HSCJ115252+004733 (More et al 2017) 3 . We include two new lens candidates, HSCJ091148+041852 and HSCJ141136−010216, found by YattaLens but missed in Chitah's classification 4 , for X-shooter spectroscopic followup.…”
Section: Other Candidatesmentioning
confidence: 86%
“…They also measured the lens redshift to be z l = 0.551 from FORS1 observations and inferred a possible AGN source redshift of z s = 3.14 from the u* drop-out criterion and a candidate Ly-alpha line. Anguita et al (2009) found that an SIE with a small amount of external shear (γ = 0.038) provides an adequate fit to the observed positions of the quasar images in COSMOS 5921+0638.…”
Section: Observations Of Cosmos 5921+0638mentioning
confidence: 89%
“…Falco et al (1999). References for full table available only at CDS: Morgan et al (2003Morgan et al ( , 2004, Johnston et al (2003), Biggs et al (2003), Inada et al (2003bInada et al ( , 2005Inada et al ( , 2006Inada et al ( , 2007Inada et al ( , 2010Inada et al ( , 2012Inada et al ( , 2014, Wisotzki et al (2004), Pindor et al (2004), Oguri et al (2005), McKean et al (2005, Eigenbrod et al (2006), Bolton et al (2006), Morokuma et al (2007), Blackburne et al (2008), Jackson (2008), Anguita et al (2009), Ghosh & Narasimha (2009)…”
Section: Discussionmentioning
confidence: 99%